Strategi Badan Usaha Milik Desa (BUMDes) dalam Mengembangkan Wisata Taman Ghanjaran di Desa Ketapanrame Kecamatan Trawas Kabupaten Mojokerto - Novia Cahyaningrum; Tukiman Tukiman (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Regional development will continue to be implemented and become one of the government's initial directions for the welfare of the community. Due to the fact that regional development in Indonesia is still uneven and not maximized, this can be seen from the increasing number of poverty in Indonesia. Especially in underdeveloped areas such as areas in villages. The purpose of this research is to describe and analyze the BUMDes Strategy in Developing Ghanjaran Park Tourism in Ketapanrame Village, Trawas Mojokerto. The type of research used is descriptive qualitative. In this study using data collection techniques used by conducting interviews with informants, observations, and documentation. Furthermore, the data analysis model in this study uses an interactive data analysis model consisting of data collection, data presentation, data condensation, and drawing conclusions. The results of this study explain that the BUMDes Ketapanrame has carried out a strategy that focuses on optimally developing tourism destinations. And strategies that focus on managing human resources, tourism institutions and the creative economy in producing superior and competitive human resources have not been implemented optimally by BUMDes Ketapanrame at Taman Ghanjaran Tourism.